DIGITAL COMMUNITY EMPOWERMENT FOR INCOME INVESTMENT DEVELOPMENT (CASE STUDY OF THE WEST JAVA KADIN FOSTERED MSME COMMUNITY) - R. Susanto Hendiarto; Elvira Nurhaliza (SEAN Institute, 2023)
The current problem is that MSME income is still far from expectations, allegedly because investment development which was previously expected to be a stimulus to generate income has not shown encouraging things, it is also suspected that digital competence for the MSME community has not been empowered. This study aims to determine the effect of digital community empowerment on investment development and its implications for the income of the MSME community, a case study on UMKM assisted by Kadin Jabar in Bandung. The representative sample is 50 respondents, and the research methodology employed is an analytical descriptive survey approach. The factors examined by each respondent possess income, investment development, and virtual community mobilization. Additionally, qualitative information is the sort of information gathered. The results of the study show that empowering digital communities has a significant effect on investment development. investment development has a significant and significant effect on income. The implication is that digital literacy needs to be implemented programmatically and massively throughout the Kadin Jabar MSME community. The point of the study is to determine why further research based on a more diversified sampling with a longer length is essential to allow results to be generalized. The respondent sample employed in this study is still restricted to UMKM, helped by Kadin Jabar in Bandung.